2021
DOI: 10.6061/clinics/2021/e2567
|View full text |Cite
|
Sign up to set email alerts
|

Microablative fractional radiofrequency as a therapeutic option for vulvar lichen sclerosus: a pilot study

Abstract: OBJECTIVES: To assess the clinical response to and the histomorphometric effects of microablative fractional radiofrequency (MFR) in women with symptomatic vulvar lichen sclerosus (VLS). METHODS: This was a pilot study on the use of MFR for the treatment of VLS. Upon recruitment and at each treatment session, all participants were examined and each of their symptoms were rated on a visual analog scale. After the procedure, the participants completed a satisfaction quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Radiofrequency is a type of high-frequency electromagnetic wave that has been widely used to treat tumors in the brain, liver, breast, thyroid, and other tissues in clinical practice. In recent years, its use in the of uterine leiomyomas of less than 5 cm has received satisfactory results ( 13 ). Electromagnetic waves act on the dermis and exert a thermal effect, resulting in vasodilation, accelerating blood flow, and increasing the permeability of the vascular endothelial cell membrane, improving the nutritional status of microvessels and nerve endings in the dermis so that the nerve terminals are no longer abnormally excited, and pruritus symptoms do not appear in the vulva.…”
Section: Discussionmentioning
confidence: 99%
“…Radiofrequency is a type of high-frequency electromagnetic wave that has been widely used to treat tumors in the brain, liver, breast, thyroid, and other tissues in clinical practice. In recent years, its use in the of uterine leiomyomas of less than 5 cm has received satisfactory results ( 13 ). Electromagnetic waves act on the dermis and exert a thermal effect, resulting in vasodilation, accelerating blood flow, and increasing the permeability of the vascular endothelial cell membrane, improving the nutritional status of microvessels and nerve endings in the dermis so that the nerve terminals are no longer abnormally excited, and pruritus symptoms do not appear in the vulva.…”
Section: Discussionmentioning
confidence: 99%
“…RF therapy has been widely used to treat dermatological and gynecological conditions. The microablative fractional-type RF, which is used to improve skin, vaginal, and vulvar mucosal trophism 19 , results in promising responses in neocollagenesis and neoelastinogenesis 20,21 , consequently leading to clinical improvement. Thus, it is observed that this therapy provides a less invasive treatment for women with SUI and MUI [11][12][13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits of micro-ablative fractional radiofrequency (MFR) on epithelial trophism and symptom improvement have been assessed in VLS patients [217]. After two to three sessions of MFR, most participants reported an improvement in symptoms, which persisted for about 11 months (range: 7-16 months) after the treatment.…”
Section: Lasermentioning
confidence: 99%